Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(\frac{9}{2}-\frac{5}{2}\right)-\frac{3}{4}=\frac{4}{2}-\frac{3}{4}=\frac{8}{4}-\frac{3}{4}=\frac{5}{4}\)\(\frac{5}{4}\)
\(\frac{9}{2}-\left(\frac{5}{2}+\frac{3}{4}\right)=\frac{9}{2}-\left(\frac{10}{4}+\frac{3}{4}\right)=\frac{9}{2}-\frac{13}{4}=\frac{18}{4}-\frac{13}{4}=\frac{5}{4}\)
Vậy : \(\left(\frac{9}{2}-\frac{5}{2}\right)-\frac{3}{4}=\frac{9}{2}-\left(\frac{5}{2}+\frac{3}{4}\right)\)
tk mk nha
a] 4/12 ; 5/12 ; 11/2 ; 1/4
b] 1 ; 9/12; 12/5 ; 11/3
c] 8/21; 6/11;8/7
d] 2/3 ;2/7 15/2
a]1/3 5/12 11/2 1/4
b]1 3/4 12/5 33/9
c]8/21 6/11 8/7
d]2/3 2/7 15/2
a) \(\frac{3}{7}+\frac{2}{5}+\frac{1}{3}=\frac{3\cdot15}{7\cdot15}+\frac{2\cdot21}{5\cdot21}+\frac{1\cdot35}{3\cdot35}\)
\(=\frac{45}{105}+\frac{42}{105}+\frac{35}{105}=\frac{45+42+35}{105}=\frac{122}{105}\)
b) \(6-\left(\frac{3}{4}+\frac{2}{7}\right)=6-\left(\frac{21}{28}+\frac{8}{28}\right)=6-\frac{29}{28}=\frac{139}{26}\)
c) \(\frac{8}{9}-\frac{3}{7}:\frac{2}{9}\cdot\frac{3}{4}=\frac{8}{9}-\frac{27}{14}\cdot\frac{3}{4}=\frac{8}{9}-\frac{81}{56}=-\frac{281}{504}\)
hok tốt
.....
\(\frac{3}{7}+\frac{2}{5}+\frac{1}{3}\)
\(=\frac{29}{35}+\frac{1}{3}\)
\(=\frac{122}{105}\)
\(6-\left(\frac{3}{4}+\frac{2}{7}\right)\)
\(=6-\frac{29}{28}\)
\(=\frac{139}{28}\)
\(\frac{8}{9}-\frac{3}{7}\div\frac{2}{9}\times\frac{3}{4}\)
\(=\frac{8}{9}-\frac{27}{14}\times\frac{3}{4}\)
\(=\frac{8}{9}-\frac{81}{56}\)
\(=-\frac{281}{504}\)
`2/3 + 4/3 + 9/3=(2+4)/3 + 9/3= 6/3 + 9/3=(6+9)/3=15/3=5`